Reactive Oxygen Species and Oxidative Stress in the Pathogenesis and Progression of Genetic Diseases of the Connective Tissue - Gustavo Egea; Francesc Jiménez-Altayó; Victoria Campuzano (Antioxidants, 2020)
Connective tissue is known to provide structural and functional “glue” properties to other tissues. It contains cellular and molecular components that are arranged in several dynamic organizations. Connective tissue is the focus of numerous genetic and nongenetic diseases. Genetic diseases of the connective tissue are minority or rare, but no less important than the nongenetic diseases. Here we review the impact of reactive oxygen species (ROS) and oxidative stress on the onset and/or progression of diseases that directly affect connective tissue and have a genetic origin. It is important to consider that ROS and oxidative stress are not synonymous, although they are often closely linked. In a normal range, ROS have a relevant physiological role, whose levels result from a fine balance between ROS producers and ROS scavenge enzymatic systems. However, pathology arises or worsens when such balance is lost, like when ROS production is abnormally and constantly high and/or when ROS scavenge (enzymatic) systems are impaired. These concepts apply to numerous diseases, and connective tissue is no exception. We have organized this review around the two basic structural molecular components of connective tissue: The ground substance and fibers (collagen and elastic fibers).